Potential Impact of Anemia on BALB/c Mice Exposed to an Extremely Low Frequency 50 Hz Magnetic Field with an Intensity of 100 μT and 500 μT - Sudarti, Sudarti; Prihandono, Trapsilo; Restanti, Revi (Jurnal Penelitian Pendidikan IPA, 2024)
Exposure threshold values (ELF MF) according to WHO, 100 μT for the public and 500 μT for workers, are still being debated. This study examines the potential impact of anemia in BULB/C mice exposed to ELF MF intensities of 100 μT and 500 μT. The research design used a completely randomized design with intensity and duration of exposure to ELF MF as factors. A sample of 60 male Bulb/C mice were divided into 6 groups, 2 groups exposed to ELF MF 100 μT, 2 groups exposed to ELF MF 500 μT, and 2 control groups. Indicators of anemia include the number of erythrocytes, hemoglobin levels and hematocrit using the complete blood count (CBC) method. Two Way Anova analysis (α = 5%), proved that the intensity factor had a significant effect (p < 0.05) on the number of erythrocytes, hemoglobin levels and hematocrit levels, while the length of exposure factor had no effect (p > 0.05). Conclusion: Exposure to ELF MF intensity of 100 μT for 30 days has the potential to cause anemia in BULB/c mice, but there appears to be an adaptive response due to exposure to ELF MF 500 μT